2014
DOI: 10.1038/jcbfm.2013.242
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Deficiency Ameliorates Neurovascular Damage in Experimental Ischemic Stroke

Abstract: Although the innate immune response to induce postischemic inflammation is considered as an essential step in the progression of cerebral ischemia injury, the role of innate immunity mediator NLRP3 in the pathogenesis of ischemic stroke is unknown. In this study, focal ischemia was induced by middle cerebral artery occlusion in NLRP3(-/-), NOX2(-/-), or wild-type (WT) mice. By magnetic resonance imaging (MRI), Evans blue permeability, and electron microscopic analyses, we found that NLRP3 deficiency ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
308
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(323 citation statements)
references
References 39 publications
14
308
0
1
Order By: Relevance
“…In the introduction we describe studies suggesting that NLRP3 inflammasomes contribute to ischemic brain injury (8,9), but that also NLRP1 inflammasomes are implicated in several models of brain injury (6,10,11), as are AIM2 inflammasomes (12). Here, using mice deficient in specific inflammasome components, we have shown that ischemic brain injury is profoundly influenced by multiple inflammasomes and, importantly, here was independent of the canonical sensor of sterile inflammation, the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the introduction we describe studies suggesting that NLRP3 inflammasomes contribute to ischemic brain injury (8,9), but that also NLRP1 inflammasomes are implicated in several models of brain injury (6,10,11), as are AIM2 inflammasomes (12). Here, using mice deficient in specific inflammasome components, we have shown that ischemic brain injury is profoundly influenced by multiple inflammasomes and, importantly, here was independent of the canonical sensor of sterile inflammation, the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Of these inflammasomes identified to date, the best characterized, and most strongly associated with sterile inflammation, is formed by NLRP3 (7). Indeed, there are now several studies suggesting that NLRP3 inflammasomes contribute to ischemic brain injury (8,9). However, the picture is more complicated.…”
mentioning
confidence: 99%
“…1 Caspase-1 activation and interleukin-1 (IL-1) release have a central role in many disorders with an inflammatory component, 2 which comprises different diseases of the central nervous system (CNS) such as multiple sclerosis, Alzheimer disease, meningitis, or stroke. [3][4][5][6][7][8] The potential molecular signals, which activate the inflammasomes in the CNS, have already been delineated in detail before. 8,9 Thus, this overview aims at a more global, system biologic view of the potential role of the inflammasomes in CNS diseases and accounts for recent discoveries in related research fields.…”
Section: Introductionmentioning
confidence: 99%
“…During ischemic brain injury, a variety of processes such as ROS production, acidosis, K + efflux, etc., mediate the activation of the NLRP3 inflammasome and such altered physiological conditions also trigger the NLRP1 inflammasome (reviewed in [78]). NLRP3 was shown to mediate ischemic brain injury in a mouse model [79], which was later not confirmed [80]. Mice deficient in AIM2, NLRC4, or ASC had decreased infarct size and improved neurological scores and reduced activation of microglia and leukocyte recruitment, while the outcome of NLRP3 deficient mice was comparable to wild-type controls [80] in experimentally induced brain ischemia.…”
Section: Resultsmentioning
confidence: 99%